IMPLEMENTASI PENYIMPANAN BAHAN MAKANAN DAN MINUMAN PADA HOTEL BINTANG 5 DI KABUPATEN BADUNG - Yulanda, I Gusti Ayu Vinka; Tuwi, I Wayan; Mareni, Ni Ketut (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Storage is one process of procurement of goods that has an important role, namely maintaining the quantity and quality of foods and beverages in the storage room in order to reduce the risk of damage and prevent waste. This research was conducted in 5-star hotels in South Kuta District Badung Regency. This research aims to find out and compare the implementation of food and beverage storage in 5-star hotels in South Kuta District Badung Regency with the concept. The type of data used in this research is qualitative data with data analysis techniques, namely qualitative descriptive. The technique of data collection is through questionnaires. The result of this research show that in the storage of foods, there are still indicators that have not been fully implemented according to the concept, namely temperature, cleanliness, location of storage rooms, and date and price labels. Meanwhile, in the storage of beverage, there are temperature indicator that have not been fully implemented according to the concept.